Case report: Patient specific combination of surgery and immunotherapy in advanced squamous cell carcinoma of the head and neck – a case series and review of literature - Olmos, Manuel; Lutz, Rainer; Büntemeyer, Tjark-Ole; Glajzer, Jacek; Nobis, Christopher-Philipp; Ries, Jutta; Möst, Tobias; Eckstein, Markus; Hecht, Markus; Gostian, Antoniu-Oreste; Erdmann, Michael; Foerster, Yannick; et al. (Frontiers in Immunology, 2022)
Background: Prognosis of patients with recurrent or metastatic head and neck cancer is generally poor. Adjuvant immunotherapy (IT) featuring immune checkpoint inhibition (ICI) is standard of care in advanced stage head and neck squamous cell carcinoma (HNSCC) and cutaneous squamous cell carcinoma (CSCC). ICI response rates in CSCC are described as higher than in HNSCC. IT is constantly shifting into earlier disease stages which confronts the surgeon with immunotherapeutically pre-treated patients. It is therefore becoming increasingly difficult to assess which patients with symptomatic tumour disease and a lack of curative surgical option might benefit from salvage surgery. Case Presentations: The following 6 cases describe therapeutic decision-making regarding ICI and (salvage) surgery in patients with advanced stage HNSCC or CSCC. Cases A and B focus on neoadjuvant ICI followed by salvage surgery. In Cases C and D salvage surgery was performed after short-term stabilisation with partial response to ICI. The last two cases (Cases E and F) address the surgical approach after failure of ICI. All cases are discussed in the context of the current study landscape and with focus on individual decision-making. For better understanding, a timetable of the clinical course is given for each case. Conclusions: ICI is rapidly expanding its frontiers into the neoadjuvant setting, frequently confronting the surgeon with heavily pretreated patients. Salvage surgery is a viable therapeutic concept despite the rise of systemic treatment options. Decision-making on surgical intervention in case of a salvage surgery remains an individual choice. For neoadjuvant ICI monitoring regarding pathological tumour response or tumor necrosis rate, we suggest correlation between the initial biopsy and the definite tumour resectate in order to increase its significance as a surrogate marker. Scheduling of neoadjuvant ICI should be further investigated, as recent studies indicate better outcomes with shorter time frames.